Changes in torque-angle profiles of the hamstrings and hamstrings-to-quadriceps ratio after two hamstring strengthening exercise interventions in female hockey players - Delextrat, A.; Bateman, J.; Ross, C.; Harman, J.; Davis, L.; Vanrenterghem, J.; Cohen, D. D. (The Journal of Strength and Conditioning Research, 2020)
The aim of this study was to compare the effects of 2 hamstring strengthening interventions (Nordic hamstrings [NHE] vs. eccentric leg curl [ELC]) on the hamstring torque-angle profiles and functional hamstrings-to-quadriceps ratio (Hecc:Qcon) in female hockey players. Female university-level players were randomly allocated to an NHE group (n = 9, 19.7 ± 1.4 years; 168.4 ± 4.4 cm; 66.2 ± 7.2 kg, 26.0 ± 4.4%), an ELC group (n = 8, 19.5 ± 1.0 years; 168.1 ± 3.4 cm; 66.7 ± 4.5 kg, 24.8 ± 3.5%), or a control (C) group (n = 8, 19.6 ± 1.4 years; 169.9 ± 7.5 cm; 70.7 ± 13.0 kg, 25.9 ± 5.2%). They performed baseline isokinetic concentric strength tests of the quadriceps (Qcon) and eccentric strength of the hamstrings (Hecc) at 120°·s-1, followed by a 6-week intervention with exercises (NHE or ELC) performed 3 times weekly, before post-tests. Analyses of variance with repeated measures were used to assess the effects of knee position angle (from 90° of knee flexion to 10° close to extension), group, and time on Qcon, Hecc, and Hecc:Qcon. There were no interactions between independent variables. Significant increases in Hecc and Hecc:Qcon were shown after NHE (+29.9 and +27.8%) and ELC (+30.5 and +38.3%) in the nondominant leg only. Furthermore, significant shifts in the hamstring eccentric angle of peak torque toward a longer muscle length were shown in both legs (14.3-28.6%). These findings suggest that NHE and ELC both resulted in significant improvements in peak and muscle-length-specific neuromuscular risk factors in the nondominant (ND) limb, thereby reducing interlimb peak strength asymmetries. Strength and conditioning specialists could therefore use both the NHE and ELC exercises in female hockey players.